The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1111/hdi.12240
|View full text |Cite
|
Sign up to set email alerts
|

Does the extracorporeal blood flow affect survival of the arteriovenous vascular access?

Abstract: Hemodiafiltration with high-convective volumes is associated with improved patient survival, whereby practical realization is contingent on high extracorporeal blood flow (Qb) and dialysis treatment time. However, Qb is restricted by vascular access (VA) quality and/or concerns that high Qb could damage the VA. Taking VA quality into consideration, one can investigate the relationship between Qb and VA survival. We analyzed data from 1039 patients treated by hemodiafiltration over a 21-month period where acces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…These results indicate that optimal blood flow rates between 300 and 400 mL/min exist, where the risk of IH can be minimized. This is in agreement with the results of Ponce et al who found that patients were at a significantly higher risk of vascular access failure for blood flow rates below 310 mL/min and greater than 400 mL/min.…”
Section: Discussionsupporting
confidence: 93%
“…These results indicate that optimal blood flow rates between 300 and 400 mL/min exist, where the risk of IH can be minimized. This is in agreement with the results of Ponce et al who found that patients were at a significantly higher risk of vascular access failure for blood flow rates below 310 mL/min and greater than 400 mL/min.…”
Section: Discussionsupporting
confidence: 93%
“…This is linked to the transitional flow in the VN, where Reynolds numbers range between 924 and 1847, indicating that an optimum blood flow rate exists which can minimize RRT. Ponce et al [33] showed patients were at a significantly higher risk of AVF failure at blood flow rates below 310 ml/min and greater than 400 ml/min. Sharp needle angles and a needle tip placed near the roof of the vein also produced regions of higher residency time as these parameters influenced the production of secondary flows.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it seems important to mention that the increase of Qs is not devoid of risks, especially the increase in the risk of dysfunction of the arteriovenous fistula [12] and an increase in the rate of formation of microbubbles [13], most of which are blocked by bubble traps under conventional HD and missing in the NxStageR system 1 device.…”
Section: Discussionmentioning
confidence: 99%